Australian Travellers in the South Seas - Halter, Nicholas (Pacific Series, 2021)
This book offers a wide-ranging survey of Australian engagement with the Pacific Islands in the late 19th and early 20th centuries. Through over 100 hitherto largely unexplored accounts of travel, the author explores how representations of the Pacific Islands in letters, diaries, reminiscences, books, newspapers and magazines contributed to popular ideas of the Pacific Islands in Australia. It offers a range of valuable insights into continuities and changes in Australian regional perspectives, showing that ordinary Australians were more closely connected to the Pacific Islands than has previously been acknowledged. Addressing the theme of travel as a historical, literary and imaginative process, this cultural history probes issues of nation and empire, race and science, commerce and tourism by focusing on significant episodes and encounters in history. This is a foundational text for future studies of Australia's relations with the Pacific, and histories of travel generally.